Studies on breeding of Sargassum vachellianum on artificial reefs in Gouqi Island, China - Chai, Zhaoyang; Huo, Yuanzi; He, Qing; Huang, Xiwen; Jiang, Xingpei; He, Peimin (Aquaculture, 2014)
The breeding of Sargassum vachellianum on artificial reefs was firstly performed in the Gouqi Island coast, Zhejiang Province, China. A new algal reef with pedestal and breeding boards was designed and produced for breeding S. vachellianum. The adult male and female plants with receptacles were collected and cultured in a breeding room for 7days for eggs releasing out of conceptacles and for fertilizing. Approximately 3.41million fertilized eggs were collected, and then sprayed evenly onto 105 breeding boards in 3 tanks for breeding. Fertilized eggs then sank and were attached on the bottom breeding boards for germination. After 35days of culture, the seedlings' average length reached approximately 5mm. And then, one hundred and five breeding boards with seedlings were transported to the Houtou coast of Gouqi Island by boats, and 21 artificial algal reefs (five breeding boards to one pedestal) were installed underwater at both Site A (slow current) and Site B (rush current). After being cultivated for 45days in the open sea, the average length and density of seedlings on artificial reefs at Site A and Site B were 31.85±0.62 and 41.31±1.39mm, 4.70±1.40 and 5.19±2.65seedlingsdm−2, respectively. One year later, the length of the plants on artificial algal reefs in the Gouqi Island coast reached up to 15.51±3.42cm. All the results indicated that large scale artificial breeding of S. vachellianum with artificial algal reefs was feasible. •An artificial large scale breeding technology of Sargassum vachellianum•A new artificial algal reef is designed and made for S. vachellianum breeding.•Seedlings of S. vachellianum on algal reefs are cultured into plants in coast.